2008
DOI: 10.1200/jco.2007.15.1126
|View full text |Cite
|
Sign up to set email alerts
|

Improved Staging of Patients With Carcinoid and Islet Cell Tumors With 18F-Dihydroxy-Phenyl-Alanine and 11C-5-Hydroxy-Tryptophan Positron Emission Tomography

Abstract: (18)F-DOPA PET/CT is the optimal imaging modality for staging in carcinoid patients and (11)C-5-HTP PET/CT in islet cell tumor patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
128
0
31

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 222 publications
(160 citation statements)
references
References 20 publications
1
128
0
31
Order By: Relevance
“…DOPA PET appears to show promise in the evaluation of pancreatic NETs. Koopmans et al [94] in the evaluation of 23 patients with pancreatic islet cell tumors reported a sensitivity of 89% using 18F-DOPA PET, as compared with 78% and 87% for gamma-based SRS and conventional CT, respectively.…”
Section: Tan Eh Et Al Imaging Of Gastroenteropancreatic Netsmentioning
confidence: 99%
“…DOPA PET appears to show promise in the evaluation of pancreatic NETs. Koopmans et al [94] in the evaluation of 23 patients with pancreatic islet cell tumors reported a sensitivity of 89% using 18F-DOPA PET, as compared with 78% and 87% for gamma-based SRS and conventional CT, respectively.…”
Section: Tan Eh Et Al Imaging Of Gastroenteropancreatic Netsmentioning
confidence: 99%
“…11 C-5-HT and 18 F-DOPA may have a role in patients with pancreatic and intestinal NENs that have negative or inconclusive results on SSTR-based imaging (Koopmans et al 2008).…”
Section: R166mentioning
confidence: 99%
“…In the case of negative SRS results, a PET/CT examination should be considered after the administration of 18 FDOPA, and for G2 and G3 NENs, PET/CT scan after the administration of 18 FDG [22,23].…”
Section: Other Imaging Examinationsmentioning
confidence: 99%